The relationship between oral health status, loneliness, and sleep quality among the migrant elderly following children in Weifang, Shandong Province, China: A comparative analysis on different migration types - Jiang, Xiaoxu; Liu, Guangwen; Xu, Jing; Li, Hexian; Wang, Jieru; Pang, Mingli; Li, Shixue; Xu, Lingzhong; Guo, Xiaolei; Kong, Fanlei (Frontiers in Public Health, 2023)
Background The migrant elderly following children (MEFC) are a vulnerable group that emerged during fast urbanization in China. The MEFC faced physical and psychological discomfort upon their arrival in the inflow city, particularly those who came from rural areas. Objective This study aimed to explore the relationship between oral health status, loneliness, and sleep quality among the MEFC in China and to clarify the disparities in the above mentioned relationship by migration type. Methods In 2021, a cross-sectional survey was conducted in Weifang, Shandong Province, using multistage cluster random sampling to collect data from the MEFC aged 60 years and over. In total, 613 respondents [525 rural-to-urban (RTU) and 88 urban-to-urban (UTU)] were included in the final database. The chi-square test, t-test, and structural equation modeling (SEM) were used to investigate the relationship between oral health status, loneliness, and sleep quality among the RTU and UTU MEFC. Results Total scores [mean ± standard deviation (SD)] for oral health status, loneliness, and sleep quality were 54.95 ± 6.47, 8.58 ± 3.03, and 4.47 ± 3.60, respectively. SEM revealed that, among the RTU and UTU MEFC, oral health status was positively and significantly related to sleep quality; however, the correlation was slightly stronger in the UTU MEFC. In both groups, there was a significant negative correlation between oral health status and loneliness, which was stronger in the UTU MEFC. In the RTU MEFC, a significant negative correlation between loneliness and sleep quality was observed, and in the UTU MEFC, no significant association between loneliness and sleep quality was observed. Conclusion The sleep quality among the MEFC in this study was higher compared to previous studies. Oral health status was negatively correlated with loneliness and positively associated with sleep quality, whereas loneliness was negatively correlated with sleep quality. These three associations differed significantly between the UTU and RTU MEFC. The government, society, and families should take measures to improve oral health and reduce loneliness among the MEFC to improve their sleep quality.